PERKEMBANGAN DAN KEBUTUHAN RUANG TERBUKA HIJAU PUBLIK DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2000-2018 - anisa mardiah; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2020)
This research aims to. 1) map the development of public green open space in 2000-2018 in Tampan District. 2) calculate the need for public green open space in the Tampan sub-district. 3) make an alternative map of meeting public green open spaces in the District of Tampan. This type of quantitative descriptive research using the overlay method produces a map of development and needs of public green space where the results of this study are: 1) map of the development of public green open space in 2000-2018 in Tampan District. 2) the amount of green open space needs in the Tampan Subdistrict level based on the number of residents and built up land, the village office level based on the number of residents and the built up land and the citizens associations level based on the built up land. 3) alternative map of fulfilling public green open space in Tampan Sub-District level based on population and citizens associations level based on built up land which is still not fulfilled by public green space. This study found that the development of public green open space in 2000-2018 developed rapidly with a total change of 6,347.43 Ha. While for the needs of public green open space in Tampan sub-district based on the number of residents fulfilled +50.68 Ha and based on the built land it was insufficient with an area of ​​-546.28 Ha. The alternative for fulfilling public green space that has not been met is to do planning on underbrush land that has not been utilized.